Study of the Sorption Properties of Natural Zeolite in Relation to Indium(III) and Gallium(III) Cations on the Model Systems - Gita Sultanbayeva; Aktolkyn Agatayeva; Raushan Kaiynbayeva; Nazym Kozhabekova; Raisa Chernyakova; Umirzak Jussipbekov (Crystals, 2022)
This paper presents the systematic studies of the sorption capacity of natural zeolite with respect to In3+ and Ga3+ cations in the model systems “natural zeolite–In3+–H2O” and “natural zeolite–In3+–Ga3+–H2O”, while varying a number of the main process factors. The patterns of sorption of In3+ and Ga3+ cations by the natural zeolite of the Shankanai deposit are revealed, depending on the zeolite vs. solution ratio, temperature, and time. It is shown that the sorption of In3+ cations by natural zeolite can be controlled by the process duration. The longer the process, the less the sorption by natural zeolite. It has been found that the sorption of In3+ cations in the “natural zeolite–In3+–Ga3+–H2O” model system depends on the amount of zeolite and temperature, and the sorption of Ga3+ cations depends on the temperature and time. The physicochemical characteristics of the spent sorbents confirm the sorption of the cations, present in the systems under study.